THE CULTURAL VALUE OF MAPALUS AND ITS RELATIONSHIP TO RELIGIOUS MODERATION IN NORTH MINAHASA REGENCY ALONG WITH ITS RELEVANCE TO CHRISTIAN EDUCATION - Meily M Wagiu; Olivia C Wuwung; Alon Mandimpu Nainggolan; Febri K Manoppo (Al-Qalam, 2023)
This study aimed to analyze and to describe values in Mapalus culture and its relation with religious moderation as a contribution for strengthening religious moderation based on local wisdom. A descriptive qualitative method was used in this study. It was found that: Firstly, Mapalus was a culture of Minahasan tribe consisting of the values of solidarity, cooperation, honesty, equality, and mutual respect which were useful in the life of the plural society. These values were relevant with the four indicators of religious moderation reinforcement, especially in tolerance, in being accommodative toward local culture and anti-harmful. Secondly, North Minahasa had a harmonious interreligious social relation according to the government, cultural practitioners, religionists, and the local communities. Thirdly, the efforts made by the community in order to implement Mapalus culture in North Minahasa corresponded to religious moderation, namely, solidarity in joy and sorrow, church constructions, and security on religious holidays. To maintain the harmonious interreligious relations in North Minahasa, it was very significant to make the values contained in Mapalus culture as the basis for strengthening religious moderation.